Aesthetic and Functional Outcomes of Open Carpal Tunnel Release and Thread Carpal Tunnel Release: A Randomized Clinical Trial - Mohammad-Reza Akhoondinasab; Amir Saraee; Hossein Akbari; Siamak-Farokh Forghani; Babak Naderi (Indian Journal of Plastic Surgery)
Background and Objectives Surgical techniques for carpal tunnel release (CTR) have gradually become less invasive. No substantial evidence supports replacing the open carpal tunnel release (OCTR) with novel minimally invasive approaches. Thread carpal tunnel release (TCTR) is a new minimally invasive CTR method associated with promising results. This study aimed to compare the aesthetic and functional outcomes of OCTR with TCTR.